Dialysis complications in acute kidney injury patients treated with prolonged intermittent renal replacement therapy sessions lasting 10 versus 6 hours: results of a randomized clinical trial - Albino, Bianca Ballarin [UNESP]; Balbi, André Luis [UNESP]; Abrão, Juliana Maria Gera [UNESP]; Ponce, Daniela [UNESP] (Wiley-Blackwell, 2015)
Prolonged intermittent renal replacement therapy (PIRRT) has emerged as an alternative to continuous renal replacement therapy in the management of acute kidney injury (AKI) patients. This trial aimed to compare the dialysis complications occurring during different durations of PIRRT sessions in critically ill AKI patients. We included patients older than 18 years with AKI associated with sepsis admitted to the intensive care unit and using noradrenaline doses ranging from 0.3 to 0.7 mu g/kg/min. Patients were divided into two groups randomly: in G1, 6-h sessions were performed, and in G2, 10-h sessions were performed. Seventy-five patients were treated with 195 PIRRT sessions for 18 consecutive months. The prevalence of hypotension, filter clotting, hypokalemia, and hypophosphatemia was 82.6, 25.3, 20, and 10.6%, respectively. G1 was composed of 38 patients treated with 100 sessions, whereas G2 consisted of 37 patients treated with 95 sessions. G1 and G2 were similar in male predominance (65.7 vs. 75.6%, P=0.34), age (63.6 +/- 14 vs. 59.9 +/- 15.5 years, P=0.28) and Sequential Organ Failure Assessment score (SOFA; 13.1 +/- 2.4 vs. 14.2 +/- 3.0, P=0.2). There was no significant difference between the two groups in hypotension (81.5 vs. 83.7%, P=0.8), filter clotting (23.6 vs. 27%, P=0.73), hypokalemia (13.1 vs. 8.1%, P=0.71), and hypophosphatemia (18.4 vs. 21.6%, P=0.72). However, the group treated with sessions of 10h were refractory to clinical measures for hypotension, and dialysis sessions were interrupted more often (9.5 vs. 30.1%, P=0.03). Metabolic control and fluid balance were similar between G1 and G2 (blood urea nitrogen [BUN]: 81 +/- 30 vs. 73 +/- 33mg/dL, P=1.0; delivered Kt/V: 1.09 +/- 0.24 vs. 1.26 +/- 0.26, P=0.09; actual ultrafiltration: 1731 +/- 818 vs. 2332 +/- 947mL, P=0.13) and fluid balance (-731 +/- 125 vs. -652 +/- 141mL, respectively) . In conclusion, intradialysis hypotension was common in AKI patients treated with PIRRT. There was no difference in the prevalence of dialysis complications in patients undergoing different durations of PIRRT.
Keywords: Acute kidney injury; Extended dialysis; Dialysis complications